Historia Universeral, Historia Moderna - Abbade Millot (Na Typografia Rollandiana, 1787)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Hard Cover; History

Historia Universeral, Historia Moderna - Abbade Millot (Na Typografia Rollandiana, 1787)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Hard Cover; History

Obras de Fr. Luis de Granada - Granada, Luis de (1787)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage